Polyamide 6/organomontmorillonite nanocomposites based on waste materials - Szustakiewicz, K.; Gazińska, M.; Kiersnowski, A.; Pigłowski, J. (Polimery, 2011)
The article reports research on waste polyamide 6 and organomontmorillonite nanocomposites. The composites were prepared utilizing masterbatches in a twin screw co-rotating extruder. X-ray diffraction (XRD) studies revealed the exfoliation of layered silicates in polymer matrix. Tensile tests proved that the addition of five per cent of the organomontmorillonite may be regarded as a facile and cheap approach to improve the mechanical properties of waste polyamide 6.